Stormskador i stickvägsgallrade bestånd i sydvästra Sverige - Blomgren, Samuel (SLU/Southern Swedish Forest Research Centre, 2006)
A storm in January 2005 felled 75 millions cubic metres of forest in South Sweden. Previous studies of wind damage in thinned stands indicated the importance of early thinnings. The risks of wind throw increased by increasing age and height of the stands. Previous studies also indicated increasing risk of wind throw along the strip roads. The aim of the present study was to investigate wind damage in Norway spruce stands in South Sweden in relation to time of the first thinning and different pattern of strip roads (width, length and direction). The stands used in the study were selected among stands with a certain amount of wind damage and thus the results were not representative for all kinds of thinning stands The data presented in this study were collected in privately owned forest estates in the southwest of Sweden. The data was collected by an objective inventory on temporary plots in Norway spruce stands thinned for the first time during a 6 year period before the storm. Based on the results, the study showed that the risk of wind throw were high just after a thinning but the risk decreased with increasing time after thinning. The study also showed that the risk of wind throw increased by increasing share of strip roads in relation to the total stand area. The risk for wind damage decreased with increasing distance between the strip roads while the width of the strip roads didn´t affect the risk. The edges of the strip roads were more exposed the wind damage compared to the stands between the roads but they also became more wind stabile with increasing time after thinning. The results were discussed in relation to previous studies of wind damage in thinned stands.